Macro-scale analysis of large scale PEM fuel cell flow-fields for automotive applications - S. Shimpalee (2018)
© The Author(s) 2017. Published by ECS. All rights reserved. The objective of this work is to establish the design principles for a proton exchange membrane fuel cell in automotive applications. In this work, the macro-scale analysis was considered to create the overall design principle. A combination of experiments and numerical simulations were carried out and the results analyzed to enhance understanding of the behavior of the large-scale 300-cm2proton exchange membrane fuel cell under automotive operations. A three-dimensional computational fluid dynamics-based methodology was used to predict such as the current and temperature distributions of this design as a function of anode relative humidity. The effect of flow direction and the cooling pattern on this design was also taken into account to enhance the understanding for this selected flow-field design. The predictions show that the gas flow and cooling directions are important dependent variables that can impact the overall performance and local distributions.